Temporal Data Mining. - Mitsa, Theophano (Chapman & Hall/CRC data mining and knowledge discovery series., 2010)
Temporal data mining deals with the harvesting of useful information from temporal data. This book covers the theory of this subject as well as its application in a variety of fields. It discusses the incorporation of temporality in databases as well as temporal data representation, similarity computation, data classification, and clustering.